2016
DOI: 10.3928/1081597x-20160523-02
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Femtosecond Laser-Assisted Endokeratophakia Using Cryopreserved Allogeneic Corneal Lenticule

Abstract: The endokeratophakia procedure using allogeneic cryopreserved lenticules was clinically stable and could be reversed. The wound healing response was mild, limited, and produced no scars. [J Refract Surg. 2016;32(8):569-576.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Lenticule implantation and re-implantation has previously been examined in rabbits [22][23][24] and non-human primates 17,25 to evaluate the refractive correction and viability of the implanted tissue. A previous study in monkeys found that 83% of the intended correction was reached 6 months after autologous 4.00 D lenticule implantation at 100-µm depth.…”
Section: Discussionmentioning
confidence: 99%
“…Lenticule implantation and re-implantation has previously been examined in rabbits [22][23][24] and non-human primates 17,25 to evaluate the refractive correction and viability of the implanted tissue. A previous study in monkeys found that 83% of the intended correction was reached 6 months after autologous 4.00 D lenticule implantation at 100-µm depth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhang et al explored the feasibility of remodeling the dioptric system by implanting an allogeneic lenticule into the corneal stromal pocket of rabbits, and found that the refractive status shifted to myopia after implantation of positive lenses. Moreover, the procedure was completely reversible at 6 months after implantation and the lenticule could be re-extracted (Zhang et al, 2015;Sun et al, 2016). This novel technique was termed FS intrastromal lenticular implantation (FILI).…”
Section: Corneal Stromal Lenticule Transplantationmentioning
confidence: 99%
“…At 2-year follow-up, the regenerated CE was found to be stable. Rama et al conducted a long-term clinical (Angunawela et al, 2012) Testing FILI procedure Fresh/immediately derived from the contralateral eye Rabbit 15/15 (Zhang et al, 2015) Testing FILI procedure Cryopreserved for 3 months Rabbit 20/20 (Sun et al, 2016) Treatment of refractive anomalies Hyperopia treatment Fresh/immediately derived from the other myopic eye Human 5/5 (Sun et al, 2015) Hyperopia, presbyopia, and keratoectasiatreatment Fresh/immediately derived from a donor Monkey 3/4 (Liu et al, 2015) study involving a large sample of 112 patients with LSCD and reported a success rate of 76.6% (Rama et al, 2010). Treatment failure was associated with a lack of stem cells in the cultured limbal epithelial cells.…”
Section: Limbal Epithelial Cell Transplantationmentioning
confidence: 99%
“…For surgical management of presbyopia, the biological inlays may act as a shape changing inlay, that creates a central hyperprolate contour for near and intermediate vision 9 , similar to what is seen following implantation of the Raindrop inlay 9,14 . The inlays may be removed and replaced according to the refractive status of the patient, as previous studies using rabbits and non-human primates have shown the reversibility of the procedure in terms of refraction and corneal thickness 21,22,24 . The diameter of the biological inlay can be customized by trephining the centre of the lenticule, as the average lenticule diameter in myopic SMILE is between 5 and 7 mm.…”
Section: Introductionmentioning
confidence: 99%